The convergence of water, electricity and gas industries: Implications for PPP design and regulation - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2020)
In several countries that have privatised their utilities, power and water are separate industries regulated by sector-specific regulators. In a parallel development, desalination has become an important source of water supply in countries where there is a shortage of cheap and clean freshwater. Where the energy source is gas, the use of gas-fired power plants to supply electricity for desalination links the water, electricity and gas industries. We use the case of the financial collapse of an integrated water and power project to illustrate the problems that can arise from such convergence, and to draw lessons for firms, Public-Private Partnerships (PPPs) and regulators. A water company had successfully tendered to build a desalination plant for a water agency that would deliver an agreed volume of water per day for a 25-year period. The technology proposed was an integrated on-site power plant to supply electricity to the desalination plant as well as to the electricity grid. The business model was for profits from electricity sales to cross-subsidise water desalination costs. However, a combination of take-or-pay LNG contracts and low spot prices in a competitive electricity market led to deep operating losses. The reasons for the collapse of the business were neither technological nor operational but arose from failure to adequately manage the market risks arising from infrastructure convergence, competition, long-term rigid contractual arrangements and missing markets. The case highlights the importance of risk assessment at bidding stage and, in particular, the risks that a cross-subsidy can create. Viewed in this context, our recommendations are for regulatory convergence for converging infrastructure sectors, multi-sector risk assessments for PPP contracts, crafting flexible PPP contracts in anticipation of future adjustments, development of more liquid hedging markets and promoting competition where feasible in infrastructure sectors.